Pharmacoinformatics elucidation of potential drug targets against migraine to target ion channel protein KCNK18 - Sehgal SA; Hassan M; Rashid S (Dove Medical Press, 2014)
Sheikh Arslan Sehgal, Mubashir Hassan, Sajid Rashid National Center for Bioinformatics, Quaid-i-Azam University, Islamabad, Pakistan Abstract: Migraine, a complex debilitating neurological disorder is strongly associated with potassium channel subfamily K member 18 (KCNK18). Research has emphasized that high levels of KCNK18 may be responsible for improper functioning of neurotransmitters, resulting in neurological disorders like migraine. In the present study, a hybrid approach of molecular docking and virtual screening were followed by pharmacophore identification and structure modeling. Screening was performed using a two-dimensional similarity search against recommended migraine drugs, keeping in view the physicochemical properties of drugs. LigandScout tool was used for exploring pharmacophore properties and designing novel molecules. Here, we report the screening of four novel compounds that have showed maximum binding affinity against KCNK18, obtained through the ZINC database, and Drug and Drug-Like libraries. Docking studies revealed that Asp-46, Ile-324, Ile-44, Gly-118, Leu-338, Val-113, and Phe-41 are critical residues for receptor–ligand interaction. A virtual screening approach coupled with docking energies and druglikeness rules illustrated that ergotamine and PB-414901692 are potential inhibitor compounds for targeting KCNK18. We propose that selected compounds may be more potent than the previously listed drug analogs based on the binding energy values. Further analysis of these inhibitors through site-directed mutagenesis could be helpful for exploring the details of ligand-binding pockets. Overall, the findings of this study may be helpful for designing novel therapeutic targets to cure migraine. Keywords: migraine, bioinformatics, modeling and docking, KCNK18, TRESK, virtual screening, pharmacoinformatics